A Perspective on Brazilian Forest Policies and Management:Are there some Lessons for India? - Gairola, Suresh Chandra (Indian Forester, 2016)
There are striking similarities in evolution of forest policies and management in India and Brazil. This paper deals with the analysis of Brazilian forest laws, policies, significant forest management practices, institutional arrangements and participation of communities and civil society with the objective of exploring the possibilities of adopting the same in Indian context. The study reveals that Brazil has no single comprehensive national forest policy like India but it comprises of environmental, agricultural, industrial, indigenous, and timber related decrees, laws and mandates. It enacted Public Forest Management Law in 2006 which brought about far reaching changes in Brazilian forest policy including opening of public forests for the first time for timber harvest by private contractors through the process of forest concessions. Unlike India, there is a significantly higher level of participation of civil society and communities in policy formulation at the highest level and management of forests. The National Environmental System is a federal apex body for policy formulation comprising of multi-state and civil society representation. National Environmental Council is a consultative agency with a broad based representation. Sixty per cent (60%) of Brazilian public forests are community forests safeguarding the right of local communities to forest resources without encumbrances. Significant steps have now been taken to reduce deforestation. Brazilian Forest Service was created as late as in 2006 with the limited mandate of regulating and overseeing forest concessions, approval of management plans and imparting training, conducting research and providing technical assistance. Brazil has initiated National Forest Development Fund to be primarily financed through forest concessions and to be used for scientific forest management. Brazil has embarked upon the task of preparing National Public Forest Registry. Brazilian protected area network is much more flexible with twelve categories having varying degree of protection. Brazil has developed its own program of forest certification called CERFLOR suited for national criteria and indicators formulated by Brazilian association of technical standards. No such national certification system exists in India. Adoption of similar initiatives in Indian context will significantly contribute towards improved conservation of forests.